Impacto da osteotomia le fort i nos tecidos nasolabiais : estudo longitudinal comparativo em tomografia computadorizada cone beam - Gil, Ariane Paredes de Sousa (2022)
The aim of this study was to evaluate the nasolabial soft tissues effects of a minimally invasive Le Fort I osteotomy and compare results with two conventional Le Fort I approaches using cone beam computed tomography (CBCT) evaluation of three-dimensional (3D) volume surfaces. Three groups were evaluated: group 1, patients who underwent conventional Le Fort I osteotomy (n=30); group 2, patients who underwent minimally invasive Le Fort I osteotomy (n=30); and group 3, patients who underwent conventional Le Fort I osteotomy with ANS recontouring or removal (n=30). CBCT evaluation was performed at two time points: T0, 1 week before surgery; T1, 6 months after surgery. Results showed statistically significant differences in nasolabial area (P<0.001). Mean maxillary advancement was 4.26mm. For group 1, mean change in inter-alar width was 2.29±1.57mm; in group 2 it was 1.20±1.56mm, and group 3 was 1.84±1.76mm. For group 1, mean change in alar base width was 1.69±2.32mm; in group 2 it was 0.85±2.08mm, and group 3 was 1.21±1.83mm. The proposed less invasive surgical technique to Le Fort I osteotomy seems to better avoid negative esthetic impact in soft tissues changes in nasolabial region when compared with conventional approaches.